What are the effects of tax changes in the United Kingdom? New evidence from a narrative evaluation - James Cloyne (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper estimates the effects of tax changes on the U.K. economy. Identification is achieved by isolating the 'exogenous' tax policy shocks in the post-war U.K. economy using a narrative strategy as in Romer and Romer (2010). The resulting tax changes are shown to be unforecastable on the basis of past macroeconomic data. I find that a 1 per cent cut in taxes stimulates GDP by 0.6 per cent on impact and by 2.5 per cent over three years. These findings are remarkably similar to the corresponding estimates for the United States. The results reinforce the view that tax changes do indeed have powerful, persistent and significant effects on the economy. Finally, 'exogenous' tax changes are shown to have contributed to major episodes in the U.K. business cycle.
Keywords: E20; E32; E62; H20; N10; 330; fiscal policy; tax shocks; tax multiplier; narrative approach; business cycles; Steuerpolitik; Steuerwirkung; Wirtschaftswachstum; Konjunktur; Großbritannien